Moniliophthora roreri (Cif y Par) Evans et al. in the crop of cocoa (Scientia Agropecuaria, 2012)
More than a century, cacao (Theobroma cacao L.) in Ecuador has been an important source of income for farmers and currency for the country, becoming one of the biggest exporters worldwide. Then, gradually lost that status due to the attack of diseases, including moniliasis caused by [Moniliophthora roreri (Cif and Par) Evans et al.]. It can cause damage of up to 80% in production. Currently there is little scientific date information on its occurrence, symptoms, etiology, epidemiology, life cycle management or control strategies of that disease, by performing this review both these important topics, bringing with it to this area of knowledge.
Keywords: Moniliasis; Theobroma cacao; conidia; integrated management.